Alkali production in the mouth and its relationship with certain patient's characteristics - Valeria Veiga GORDAN; Deborah Landry McEDWARD; Marc Edward OTTENGA; Cynthia Wilson GARVAN; Pearl Ann HARRIS (University of São Paulo, 2014)
Objectives To assess the relationships among alkali production, diet, oral health behaviors, and oral hygiene. Methods Data from 52 subjects including demographics, diet, and oral hygiene scores were analyzed against the level of arginine and urea enzymes in plaque and saliva samples. An oral habit survey was completed that included: use of tobacco (TB), alcohol (AH), sugary drinks (SD), and diet. Alkali production through arginine deiminase (ADS) and urease activities were measured in smooth-surface supragingival dental plaque and un stimulated saliva samples from all subjects. ADS and urease activities were measured by quantification of the ammonia generated from the incubation of plaque or saliva samples. Spearman correlations were used to compute all associations. Results Participants in the lowest SES (Socio-economic status) group had the habit of consuming sugary drinks the most and had the highest rate of tobacco use. Males consumed significantly more alcohol than females. No significant relationship was found between age or gender and alkali production. Higher rates of sugary drink consumption and tobacco use were significantly related to lower alkali production. Conclusion The study showed a relationship between alkali production and oral hygiene, diet, and certain oral health behaviors. Poor oral hygiene was significantly associated with age, lower SES, tobacco use, and alcohol, and sugary drinks consumption. Clinical relevance Certain oral health behaviors have an impact on oral hygiene and on alkali production; it is important to address these factors with patients as a strategy for caries control.